Study of E-Waste Management in Kashmir Region (International Journal of Innovative Research in Engineering & Management, 2023)
The act of widespread, careless, and  haphazard disposal of e-waste for monetary gain, along  with government ineptitude and unorthodox systematic  supervision of it in any community, is undeniably unsafe  and destructive to the country's public health and economy  as a whole. Untreated e-waste poses a significant hazard to  public health and people's quality of life in general. It also  shatters and renders the environment unproductive for no  apparent reason. Furthermore, it is the socially and  economically weaker members of society who suffer the  most under these situations. With the growing number of  people purchasing electrical and electronic items,  numerous regions are being utilized as dumping grounds  for e-waste, and flaws in government waste management  methods have made WEEE a severe challenge. Previously,  the management of e-environmental wastes and  sustainability had a low priority. Lack of financial  resources, institutional flaws, improper technology  selection, and public unawareness towards WEEEM are  some of the elements that have led to the growing trend in  the perception of E-Waste as a concern. On the other hand,  the economic benefits of WEEE through the recovery and  recycling of materials, which can then be reused and re sold as secondary materials, is a great way for individuals  to get jobs and businesses to generate cash. The problem  of e- waste, its sources, content, and treatment as  associated garbage have all been critically examined in this  research.
Keywords: E-waste; Incineration; Kashmir; Landfilling; Treatment